Combined effects of insulin resistance and altitude of residence on 10-year risk of atherosclerotic cardiovascular disease - Xia, Yu; He, Liping; Pang, Linhong; Zhu, Wenlong; Zhang, Nan; Gao, Yue; Duo, Lin; Wang, Zhongjie; Yang, Wenhui; Tang, Mingjing; Luo, Zhiling; Zhu, Da; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe combined health effects of the triglyceride–glucose (TyG) index and altitude of residence on the 10-year risk of atherosclerotic cardiovascular disease (ASCVD) remain unknown. We examined the combined effect of the TyG index and altitude of residence on ASCVD using data from two cross-sectional studies.MethodsWe included 6,861 participants with no history of ASCVD from two cross-sectional studies and assessed their 10-year risk of ASCVD using the China-PAR model. We stratified the TyG index and altitude of residence and used multivariate-adjusted logistic models to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for a high 10-year risk of ASCVD. Both additive and multiplicative effects were considered.ResultsA total of 6,861 participants free of ASCVD at baseline were included in the analysis. Among them, 559 study participants were classified as being at high risk for ASCVD. Compared with participants with the lowest TyG index levels, those with the highest TyG index levels were more likely to be at high risk for ASCVD [(OR): 2.17, 95% C1: 1.67, 2.82]. Non-linear relationships were observed in the restricted cubic spline analyses. Altitude of residence was also associated with an increased risk of ASCVD [(OR): per standard deviation: 1.46, 95% Cl: 1.29, 1.65]. However, there was limited evidence of interaction between the TyG index and altitude of residence. Similar findings were observed in a series of sensitivity analyses.ConclusionBoth the TyG index and altitude of residence were positively associated with a high risk of ASCVD separately; however, there was no significant interaction between the associations.